Screening for potential quality markers of Callerya nitida var. hirsutissima. Z.Wei based on components profile, pharmacokinetics, and anti‐inflammatory study. Issue 2 (16th November 2021) - Chen, Jingbin; Song, Yonggui; Zhou, Mingyue; Yang, Ming; Zhang, Ling; Naeem, Abid; Li, Zexie; Deng, Yaqiong; Liu, Yali; Ai, Zhifu; Su, Dan
Abstract: Callerya nitida var. hirsutissima. Z.Wei is a classical, traditional Chinese herbal medicine mostly used to treat rheumatoid arthritis. Recent reports suggest that inconsistent and poor‐quality control levels have primarily affected the therapeutic efficacy. Therefore, the aim of the current study was to investigate the active chemical ingredients, stability of components in blood, pharmacokinetics, and pharmacodynamics to specify the potential markers for quality control and quality evaluation of Callerya nitida . The active components in vitro and in vivo were obtained by ultra‐high‐performance liquid chromatography‐mass spectrometry. Moreover, the changes of the bioactive components in the blood were monitored over time (0–24 h) in order to identify stable active components. On this basis, the pharmacokinetic characteristics of these ingredients combined with the anti‐inflammatory activity were determined to screen out the potential markers for ensuring the quality control of Callerya nitida . The identified four components, such as calycosin, daidzein, formononetin, and 5‐hydroxymethylfurfural, have the characteristics of intrinsic components, clearly defined structures, high exposure values, and in vivo stability, which are important for the therapeutic activity of pharmacologically active materials. Therefore, they can be used as potential markers to control the quality levels of Callerya nitida .